Factors specific to the process of sustainable development in Prov Iraqi Kurdistan - فتاح عبد الجبار محمود; حمد ايوب انور (Journal of Economics and Administrative Sciences, 2015)
Thoudy sustainable development attention of researchers and scholars at various orientations intellectual economies were or Ssayasn, or others as gaining the process of paramount importance in the light of major developments and unprecedented in the modern world at the levels of all and which turned the world sprawling into something like a global village is small, being aimed at elimination of backwardness and development branches of the national economy and raise the level of economic performance, and what was the province of Kurdistan-Iraq from areas with privacy clear and meets the elements of economic development has seen the movement of economic development and social with special features de facto geographical, political and social development of the province, as it reflected the political conditions on his experience this development was influenced by the experience of the nature and size of the dominant ingredient in exposed and subjected to a number of current and future challenges affecting more or less faithful to the process of sustainable development. On this basis, there is a need to study the determinants of the process of sustainable development in the Kurdistan Region - Iraq, and display the economic and social reality in the province of Kurdistan, where results indicate that the process of sustainable development in the region face a range of challenges, serious economic, environmental and social as well as the challenges of institutional and political